Plasma mediated neutrophil stimulation during coronary angioplasty: autocrine effect of platelet activating factor. Issue 6 (December 1995) - Siminiak, T.; O'Gorman, D. J.; Shahi, M.; Hackett, D.; Sheridan, D. J.
Abstract : BACKGROUND–Polymorphonuclear neutrophils are involved in the development of myocardial injury during ischaemia and reperfusion. Coronary angioplasty has been shown to result in neutrophil activation. This may be a result of contact with ligands expressed by endothelial cells or response to soluble stimuli released from ischaemic tissue into the plasma or both. OBJECTIVE–To investigate plasma mediated neutrophil activation during angioplasty. METHODS AND RESULTS–Plasma samples were collected from the coronary sinus, femoral artery, and femoral vein of 14 patients undergoing angioplasty, before and after the first balloon inflation and at the end of the procedure. Plasma samples were incubated with washed neutrophils isolated from healthy donors. Expression of the adhesion molecules CD18 integrin and L-selectin (Leu-8) was measured by flow cytometry, and superoxide anion production was measured by chemiluminescence. Plasma samples from the coronary sinus and femoral artery but not from the peripheral vein induced increased expression of neutrophil CD18 after balloon deflation. Modification of the expression of L-selectin was not noted. Production of superoxide anion by neutrophils was stimulated by plasma samples from the coronary sinus, but not by those from the femoral artery or vein. This plasma mediated neutrophil stimulation was prevented when the neutrophils were pretreated with platelet activating factor receptor antagonists BN52021 or BN50739. The platelet activating factor concentration detected in the coronary sinus was not higher than in control plasma. CONCLUSION–Brief ischaemia during coronary angioplasty leads to the release of soluble stimuli capable of inducing neutrophil integrin expression and free oxygen radical production. Platelet activating factor may act as an autocrine neutrophil stimulus under these conditions.